2000
DOI: 10.1590/s1516-89132000000300010
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia sp. in naturally infected Didelphis aurita (Wied, 1826) (marsupialia: didelphidae)

Abstract: Fifty-six opossums (Didelphis aurita) were captured on the campus of Universidade Federal Rural do Rio de Janeiro, Seropédica county, Rio de Janeiro state, in order to investigate the occurrence of Borrelia sp among them in relation with the study of spirochaetemia and its ectoparasites. Blood tests were made through dark field and phase contrast microscopy, as well as the obtainment of blood smears. Smears were stained with Giemsa stain, which did not prove efficacy. There was no relation between results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Little is known about wild reservoirs of these bacteria in Brazil, but recently, a study reported B. henselae and B. clarridgeiae in domestic cats from an Atlantic Forest area of Rio de Janeiro state (RJ), where humans, domestic, synanthropic and wild animals can easily interact (Silva et al, 2019). Opossums are often identified as likely maintainers of infectious agents with zoonotic potential (Abel et al, 2000;Ruiz-Piñaand Cruz-Reyes, 2002;Fornazari et al, 2011;Pena et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about wild reservoirs of these bacteria in Brazil, but recently, a study reported B. henselae and B. clarridgeiae in domestic cats from an Atlantic Forest area of Rio de Janeiro state (RJ), where humans, domestic, synanthropic and wild animals can easily interact (Silva et al, 2019). Opossums are often identified as likely maintainers of infectious agents with zoonotic potential (Abel et al, 2000;Ruiz-Piñaand Cruz-Reyes, 2002;Fornazari et al, 2011;Pena et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being an important component of the ecosystem and part of biodiversity, some of these ectoparasites have an extreme epidemiological importance as they act as vectors and host of various pathogenic for humans microorganisms causing world known serious diseases such as murine typhus, bubonic plague, tularemia or Lyme disease (Baker & Wharton 1952, Abel et al 2000. Although the ectoparasites of small mammals have ecologic, economic and public health importance, there are not many studies in Brazil (Graciolli et al 2006).…”
mentioning
confidence: 99%